Computer modelling of vehicle rollover crash tests conducted with the UNSW Jordan Rollover System. Issue 3 (3rd May 2016) - Mongiardini, M.; Grzebieta, R. H.; Mattos, G. A.; Bambach, M. R.
ABSTRACT: Vehicle rollovers are one of the least forgiving crash modes with one of the highest occupant fatality and serious-injury rates. A detailed understanding of the mechanisms associated to injuries resulting from vehicle rollovers is essential for the development of effective occupant-protection countermeasures during a rollover. Crash testing devices such as the Jordan Rollover System (JRS) recently have been used for investigating vehicle rollovers within a testing environment. Computer simulations of such rollover crash tests would provide a valuable support by allowing to greatly reduce the number of tests otherwise necessary for identifying the most critical test conditions as well as conducting comprehensive parametric studies. This paper describes a modelling effort to simulate vehicle rollover crash testing conducted with the University of New South Wales (UNSW) JRS, which is an improved version of the original JRS. A detailed finite element (FE) model of the UNSW JRS was coupled with FE models of both a small passenger car and a sport utility vehicle. Relevant physical phenomena that have to be modelled for successfully simulating such complex testing were initially identified. Both modelled configurations were validated against experimental rollover tests performed with the corresponding vehicle and proved to be capable of replicating the actual vehicle dynamics and deformations. Such developed FE model will be a useful tool for detailed investigations of vehicle rollover crash tests conducted with the UNSW JRS.